Air contaminant hazards assessment at graphite electrode manufacturing workplace: Dust survey and chemical exposure monitoring / Manprith Singh Sarjit Singh - Manprith Singh , Sarjit Singh (2023)
Dust emission in graphite electrode manufacturing’s during its processes has been a concern as it is associated with occupational respiratory disease and goes further than physical effects. This study aims to carry out survey for the dust emitted and the air contaminants hazards at selected workplace of a graphite electrode manufacturing at the baking process. A total of ten spots has been identified to collect the gravimetric dust. The gravimetric dust taken at total ten sampling points represents the activity area at the Baking process. Fine suspended dust particles from both primary source and secondary source contribute to the particulate loading in the atmosphere and the surrounding surfaces. This study was carried out to look into these dust emission issues and the expected health impact to the operators. Gravimetric dust survey is carried out at each process locations namely the autoloading, scrapping at the Enrima machine, bake and re-bake, pitch impregnation, cleaning of the GE with the calculated to the level of dust fall in a period of 8 hours, time weighted average. Gravimetric dust is collected to assess the amount of dust that is generated from the operations at baking process. There is also dust going airborne and the airborne dust is assessed using a calibrated equipment to assess the particulate matter at 1 μm, 2.5μm and at 10μm. Chemical exposure monitoring is carried out by competent person for the operation staffs at site. The result for gravimetric dust reading shows some processes generate more dust especially when the cleaning is carried out to the electrodes and the secondary dust gets airborne from the manual bagging process. The results show different locations of process activities generated different levels of dust. As for airborne particulate matter, the dust percentage is higher for larger particulate matter during activities at site and lower particulate matter sizes airborne at non-activity sites as the heavier dust has settled faster. Exposure monitoring was carried out by competent hygiene technician personal, which was carried out for actual operators who are exposed to these conditions and the result shows that all operation staffs are below the permissible exposure limits. It is Risk controls suggestion proposed are based on the Hierarchy of control.